Nafkah Produktif Perspektif Maqashid Syariah - Afandi, Moh. (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2021)
Nafkah produktif lahir dari kreativitas suami isteri dalam upayanya untuk menjamin kesejahteraan rumah tangga. Model nafkah ini telah berhasil menjaga keharmonisan rumah tangga, melindungi keluarga dari kesenjangan ekonomi, dan memberikan peranan sosial yang setara bagi kaum hawa. (Productive livelihoods are born from the creativity of husband and wife in their efforts to ensure household welfare. This livelihood model has succeeded in maintaining household harmony, protecting families from economic disparities, and providing an equal social role for women)